3
$\begingroup$

I have been struggling with this functional series. $$\sum_{n=1}^{\infty}{(-1)^{n-1}n^2x^n}$$ I need to calulate the sum.
Any tips would be appreciated.

$\endgroup$
  • 1
    $\begingroup$ This sort of sum can be done by "differentiating/integrating under the sum". Try differentiating or integrating each term with respect to $x$ to get rid of the factors of $n$; if it doesn't work out as is, you might need to pull some power of $x$ outside the sum first. Then when you've gotten rid of the $n^2$, you can evaluate the sum, and then you can do the inverse of the integration/differentiation that you did before to get the final result. $\endgroup$ – joriki Mar 21 '11 at 17:44
7
$\begingroup$

Try considering what happens when you differentiate the following with respect to $x$:
$1/(1+x) = 1-x+x^2-x^3+x^4...$

That should get you thinking in the right direction.

$\endgroup$
3
$\begingroup$

Note that $n^2=n(n-1)+n$ and hence the given series $\displaystyle\sum\limits_{n\geq 1} n^2 x^n=: f(n;x)$ can be written as

$f(n;x)=\displaystyle\sum_{n\geq 1} n(n-1)x^n+\displaystyle\sum_{n\geq 1} n x^n=f_1(n;x)+f_2(n;x)$ respectively. Let us determine these $f_1(n;x)$ and $f_2(n;x)$ separately.

Now $f_1(n;x)=x^2 \displaystyle\sum_{n\geq 1} n(n-1)x^{n-2}=x^2 \frac{2}{(1+x)^3}=\frac{2x^2}{(1+x)^3}$ by using the fact $(1+x)^{-1}=\displaystyle\sum_{n\geq 1} x^n$ and two times successive differentiation.

On the other hand $f_2(n;x)=-x \frac{1}{(1+x)^2}=\frac{-x}{(1+x)^2}$.

Therefore $f(n;x)=\frac{2x^2}{(1+x)^3}-\frac{x}{(1+x)^2}$

$\endgroup$
2
$\begingroup$

Hints:

If you divide your series by $x$ and then integrate it, it might be a little simpler.

Then ask yourself what you can do to make it even simpler. If you are lucky you will eventually end up with a geometric series where you know the answer.

Then undo all the steps you have taken (in reverse order), and you should have a solution to your original question.

$\endgroup$
1
$\begingroup$

Incorporate $-1$ into $x$. Now consider the derivatives of $\sum z^n$. How can you get $n^2$ to show up?

$\endgroup$
1
$\begingroup$

The ratio of convergence is $$\limsup_{n\to\infty}\frac{1}{\sqrt[n]{n^2}}=1,$$ so the series in convergent on $(-1;1)$. Now if move one $x$ factor before the sum, so that the exponent of $x$ in the sum is $n-1$, what happens if you integrate elementwise? Repeat!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.